Десантник дракой тешится: роман / С. И. Зверев - Зверев Сергей Иванович (Спецназ ВДВ, 2008)
Экземпляры: (20200716) / Инвентарный номер: 32933 / Цена: 85.40 / Сис.шифр: Р2 / Авт.знак: З-43 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6